Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1134/s0020168513140094
|View full text |Cite
|
Sign up to set email alerts
|

State of the art and problems in determining high gold contents in alloys and articles (Review)

Abstract: Methods widely used at analytical laboratories in industry for determining high gold contents (from several percent to 99.9%) in alloys, compounds, solutions, and articles, as well as the existing interna tional and national standards and publications on this topic covering 2001-2010, are reviewed. The review concentrates on publications in which the accuracy of the proposed procedures was estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The supramolecular recognition strategy described here is a new way to reversibly encapsulate precious metal coordination complexes under mild conditions. , The simple macrocyclic structure is readily amenable to modifications that enable operation in different solvents (especially water) or on the surface of solid supports. In addition to separation processes for precious metal mining, recycling, or water purification, , these new receptors will likely be useful for many other applications that involve precious metals, such as high-sensitivity detection, catalysis and process chemistry, , magnetic materials, nanoparticle fabrication, and drug delivery. , Studies are ongoing, and the results will be reported in due course.…”
mentioning
confidence: 99%
“…The supramolecular recognition strategy described here is a new way to reversibly encapsulate precious metal coordination complexes under mild conditions. , The simple macrocyclic structure is readily amenable to modifications that enable operation in different solvents (especially water) or on the surface of solid supports. In addition to separation processes for precious metal mining, recycling, or water purification, , these new receptors will likely be useful for many other applications that involve precious metals, such as high-sensitivity detection, catalysis and process chemistry, , magnetic materials, nanoparticle fabrication, and drug delivery. , Studies are ongoing, and the results will be reported in due course.…”
mentioning
confidence: 99%